The Influence of Public Ownership and Company Size on Timeliness Corporate Internet Reporting at PT. Bank Panin Dubai Syariah Tbk Year 2017-2020 - Naila Sri Sukma Ayu (Social Impact Journal, 2023)
To find out and analyze the extent of public ownership as indicated by the percentage of shares circulating among the general public and the size of the company using the benchmark of total assets owned by the company at the time of Internet company reporting, this research was conducted at PT. Bank Panin Dubai Syariah Tbk between 2017 and 2020. This research uses quantitative methodology combined with descriptive strategies. This can be seen from the official website of the Indonesian Stock Exchange during the reporting period. The PT's quarterly, annual, and annual financial reports are the data sources used in this research. With a total of eighteen analysis units, Bank Panin Dubai Syariah Tbk data for 2017–2020 was obtained from the Indonesian Stock Exchange website. The research results show that there is no significant influence between public ownership and company size on timeliness of corporate internet reporting with a significance value of 0.502.